HUMAN DIGNITY ACCORDING TO THE GOSPEL OF LUKE - DuPlessis, Johann (Scriptura, 2010)
Human dignity can be studied from two perspectives: a fundamental approach and also that of existential experience of human dignity and indignity. This study addresses both aspects. Taking into account that the first audience of Luke was mixed, but probably included a significant number of "haves", a social analysis is done to discern criteria of worthiness in the Early-Mediterranean world that is addressed by the Lucan narrative. Then follows a literary and semantic analysis of relevant passages from Luke, and finally some conclusions are drawn about Lucan perspectives on human dignity. These are: Jesus as the vantage point for bestowing dignity; dignity is assigned through association; one of the main Lucan viewpoints is that dignity involves powerlessness and vulnerability; and finally that dignity does not exclude suffering.